Effect of Blast Furnace Slag Powder on Concrete Performance - SUI Wei; CHEN Liang; XIAO Yang; XIONG Jingyu (Renmin Zhujiang)
Different dosages of blast furnace slag powder are selected for experimental research on workability, mechanical properties,abrasion resistance, frost resistance,and thermal properties of concrete.The effort is to explore the influence laws of blast furnace slag powder on concrete performance.The results show that the addition of slag powder can improve the workability of concrete.Under the experimental dosage,a larger amount of slag powder is accompanied by higher compressive strength and abrasion resistance of concrete in the later stage;the addition of 35% slag powder can increase the abrasion resistance of concrete by 2.65% while reducing the wear rate by 6.51%.The slag powder can significantly improve the frost resistance of concrete, and the addition of 35% slag powder can raise the frost resistance level of concrete to above F400.The thermal parameters and autogenous volume deformation of concrete mixed with 35% slag powder are measured to provide a technical reference for the application of blast furnace slag powder.